Studies in symbolic interaction. Vol. 24 - Denzin, Norman K. (JAI, 2001)
This volume examines the concept of performance in ethnographic studies, with a special focus on the issues surrounding the performances of race, and cultural and environmental identities. A special partial section honours the contributions of David R. Maines to the field of communication studies. The concluding section considers new theoretical developments in interaction theory, including a re-examination of the spectatorial gaze in film and literary approaches to the imagined past.